EFFECT OF CREATIVE STRATEGY PT. SAMSUNG ELECTRONICS INDONESIA PRODUCT PROMOTION ON SAMSUNG GALAXY SERIES IN PEGANGSAAN DUA AREAS NORTH JAKARTA - Siti Meisyaroh, S.Sos., M.Soc. Sc (Jurnal Ekonomi Perusahaan, 2016)
In this research the products that will be examined is the Samsung Galaxy Series. Using the concept of marketing communications, creative strategy, and promotion. The concept was used to further examine the data obtained about PT. Samsung Electronics Indonesia is in conformity with the existing concept or not. Researchers want to see whether or not the influence of the creative strategy on the suitability of the product promotion Samsung Galaxy Series. This research was conducted by using descriptive quantitative research methods, which is expected to give an idea of the influence by a creative strategy to product promotion. Data was collected by distributing questionnaires to 100 respondents which is the users of the Samsung Galaxy Series. This study has also found that there are significant creative strategies PT. Samsung Electronics Indonesia on the conformity of product promotion on the Samsung Galaxy Series. This can be seen from the results of simple linear regression, where there is a regression coefficient of 0.672 where the figure explains that an increase or decrease in the value of promotional products by 67.2% after doing creative strategy. It was concluded that the Creative Strategy PT. Samsung Electronics Indonesia has an influence on the promotion of products Samsung GalaxyÂ  Series in the region Pegangsaan 2.Keywords: Creative Strategy, Promotion of Product, influence